The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5812/jhealthscope-121797
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behaviour Among Nigerian Undergraduates: Associations with Gambling Disorder and Emotional Dysregulation

Abstract: Background: There is a high prevalence of suicidal behavior among Nigerian youths. However, the connections between suicidal behavior and precipitating factors, such as gambling disorder and emotional dysregulation (ED) in this population, are not well researched. Objectives: The present study examined the associations between gambling disorder, ED, and suicidal behavior in Nigerian university undergraduate students. Methods: This study was carried out during October 2020 - April 2021 on 1338 undergraduates wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Available systematic review of national surveys from 2000-2015 (Yu et al, 2023;Choliz and Choliz, 2016) found wide variations in GD rates for different countries; worldwide ranged from 0.12-5.8%, 0.12-3.4% in Europe. In Nigeria, evidences show that 1 in every 5 male and 1 in every 12 female youths have high to severe GD rating leading to elevated burden of mental harm (e,g., anxiety, stress, depression and in some instances suicidal deaths) (Akpunne et al, 2022). This report underscores the need to understand the underlying factors that drive GD including the environment (quality of life), person (escape outcome expectancies and craving) in order to optimize its prevention, treatment and policy.…”
Section: Introductionmentioning
confidence: 94%
“…Available systematic review of national surveys from 2000-2015 (Yu et al, 2023;Choliz and Choliz, 2016) found wide variations in GD rates for different countries; worldwide ranged from 0.12-5.8%, 0.12-3.4% in Europe. In Nigeria, evidences show that 1 in every 5 male and 1 in every 12 female youths have high to severe GD rating leading to elevated burden of mental harm (e,g., anxiety, stress, depression and in some instances suicidal deaths) (Akpunne et al, 2022). This report underscores the need to understand the underlying factors that drive GD including the environment (quality of life), person (escape outcome expectancies and craving) in order to optimize its prevention, treatment and policy.…”
Section: Introductionmentioning
confidence: 94%